Supercritical fluid recycle for surge control of CO2 centrifugal compressors - Budinis,S; Thornhill,NF (Computers & Chemical Engineering, 2016)
This paper presents computer-based design and analysis of control systems for centrifugal compressors when the operating fluid is supercritical CO2.It reports a non-linear dynamic model including a main forward compression line and two different configurations for the recycle antisurge line. Disturbance scenarios are proposed for testing the configurations and performance indicators are suggested to evaluate control performance and power consumption of the compression system.The paper demonstrates that compared to the hot recycle, the process configuration including a cold gas recycle has better overall stability, but higher power consumption and lower values for the control performance indicators. Based on the previous considerations, the paper gives suggestions regarding the choice of the recycle configuration. Moreover it compares subcritical and supercritical compression during surge prevention and highlights the importance of the selection of the gas recycle configuration when full recycle is needed.